A bibliometric analysis on cognitive processing of emotional words. (22nd April 2019) - Liu, Jia; Fan, Lin; Yin, Hongshan
Abstract: To investigate the growth of studies on emotional word processing, co-citations and co-occurring terms in related research were analyzed by using CiteSpace software. Through visualizing the references obtained from Web of Science (WoS) Core Collection of Thomson Reuters, the main research patterns and the hot research topics were identified. The research patterns include processing levels (implicit and explicit processing), the comparison between emotional and neutral words as well as visual emotional word processing under various tasks such as blink modification and subvocal rehearsal. The hot themes are: (1) the neural correlates of negative, positive and neutral words, (2) individual differences in trait anxiety, gender or eating disorders, and (3) audiovisual processing of emotional stimuli (words, faces, pictures, and sounds). Different from the previous review papers, the present study offers a new approach to visualizing relevant data over the past three decades to synthesize scientific research findings on emotional word processing. In addition, suggestions for future work in this area are provided.